An environmental evaluation system in the planning process of quarries in South Africa - Hoogervorst, Arend (Department of Environmental and Geographical Science, 2015)
The historical framework and background to the process of approving quarries for construction materials in South Africa is examined in depth. In order to produce a proposed Environmental Evaluation System for the assessment of quarries in South Africa, the interrelationships of Quarries and the Environment are briefly examined philosophically. Environmental Impact terminology and Environmental Impact Assessment methodologies, techniques and procedures are also discussed.